Sistem Penentuan Lokasi Pusat Layanan Terpadu Bagi Penderita Penyakit Demam Berdarah Dengan Menggunakan K-Means Clustering - Iski Zaliman; Tri Basuki Kurniawan; Darius Antoni (Jurnal Informatika Global)
Puskesmas is a functional organizational unit that organizes comprehensive, integrated, equitable health efforts that are acceptable and affordable to the community. The function of the puskesmas is to provide health services to the community through the Community Health Efforts (UKM) and Individual Health Efforts (UKP) programs which are at the forefront of providing health services to the community, especially the prevention and treatment of diseases. The disease is divided into 3 types namely infectious diseases or diseases caused by germs that attack the human body. This research will attempt to handle infectious diseases, namely dengue hemorrhagic fever (DHF). Dengue fever or dengue fever (abbreviated as DHF) is an infection caused by dengue virus. Mosquitoes or some types of mosquitoes transmit (or spread) dengue virus. Then a computerized analysis using data mining software that supports the flow of data and information in accordance with the needs of handling dengue fever from these processes and the selection of a more suitable method is used that is using K-Means clustering.Keywords : The location determination system, dengue faver, K-Means Clusterring